(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Aluminum oxide (AZO) thin films were deposited on glass substrates using the sol-gel dip coating method. The effect of temperature on electrical and optical conductivity properties of Al-doped ZnO thin films was studied. The ratio of the mass of Al atoms to the mass of Zn atoms was chosen to be 3%. ZnO films with Al atoms heat treated at 550℃ showed high transmittance up to 84% in the visible and near-infrared radiation fields. When Al atoms are introduced, it is found that the main charge carriers are n types.